A dokąd teraz? Problematyka obozowa w perspektywie jugosłowiańskiej. Przypadek Elviry Kohn - Taczyńska, Katarzyna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The text contains an analysis of photographs and personal (written) documents by Elvira Kohn (1914–2003), a Jew and a female prisoner of Kampor concentration camp, established in July 1942 on Rab island in Croatia. The article explores the specific features of a narrative about World War II and the Jewish experience in Yugoslavia which emerge from the materials. Presented so that they complement each other, photographs understood as photo-texts (Marianna Michałowska) and a diary and a poem recognized as inconspicuous texts (Jerzy Strzelczyk, Inga Iwasiów) form Kohn’s personal narrative. The microhistory (Ewa Domańska) of this photographer and writer is presented as material supplementing the knowledge about the past of Jews in Yugoslavia, which – due to the choices Elvira Kohn made in her life and art – can also be considered as evidence of emancipatory social changes of that period, and as an example of overcoming the existing cultural paradigms.